Disorders of Lipid Metabolism and Chronic Kidney Disease in the Elderly - Choudhury, Devasmita (2009)
The elderly population with chronic kidney disease (CKD) is at greater risk for cardiovascular disease than from an independent risk of CKD, as well as from added dyslipidemia of aging and renal dysfunction. Changes in lipid metabolism with more isodense and high-dense, triglyceride-rich particles, low high-density lipoprotein cholesterol, and increased triglyceride levels occur with CKD and aging, which are noted to have significant atherogenic potential. In addition, lipid abnormalities may lead to the progression of CKD. Cardiovascular mortality in the end-stage renal disease population is more than 10 times higher than the general population. Treatment of dyslipidemia in the general population suggests important benefits both in reducing cardiovascular risk and in the prevention of cardiovascular disease. Secondary analyses of elderly subgroups of various large prospective studies with statins suggest treatment benefit with statin use in the elderly. Similarly limited data from secondary analyses of CKD subgroups of larger prospective trials using statins also suggest a possible benefit in cardiovascular outcomes and the progression of kidney disease. However, randomized trials have yet to confirm similar benefits and targets of treatment for dyslipidemia in the elderly with CKD and end-stage renal disease. Treatment in the elderly with CKD should be individualized and outweigh risks of side effects and drug–drug interactions. There is a need for further specific investigation of dyslipidemia of CKD in the aging population in relation to renal disease progression and cardiovascular outcome.